Visualizing Sacred Narrative: A Case Study on The Intersemiotic Translation of The Book of Esther into Balinese Painting - Diana Erfiani, Ni Made; Chrisma Dewi , Putu; Octovianus L. Awololon, Yohanes (Universitas Udayana, 2026)
This study examines the intersemiotic translation of The Book of Esther into Balinese paintings in the Cheerful Good News collection published by the Indonesian Bible Society (2007). Using a qualitative case study, it analyzes how biblical narratives are reinterpreted through Balinese visual aesthetics using strategies of reduction, addition, focalization, integration, and symbolic adaptation. Each artwork is explored for textual fidelity, cultural and symbolic localization, and multimodal construction. The study highlights how simplification, substitution, and narrative emphasis reframe themes like courage, justice, and divine providence. While some narrative elements are condensed or altered, theological meanings are retained through symbolic codes and emotional framing. Rather than one-to-one equivalence, the process reflects interpretive transformation based on cultural and semiotic norms. The article contributes to translation studies and visual anthropology by applying intersemiotic frameworks within Southeast Asia, demonstrating how sacred texts are visually reimagined through local idioms rooted in religious symbolism and aesthetic tradition.